Interaction energy for a fullerene encapsulated in a carbon nanotorus - Pakhapoom Sarapat (2019)
© 2018, Springer International Publishing AG, part of Springer Nature. The interaction energy of a fullerene symmetrically situated inside a carbon nanotorus is studied. For these non-bonded molecules, the main interaction originates from the van der Waals energy which is modelled by the 6–12 Lennard-Jones potential. Upon utilising the continuum approximation which assumes that there are infinitely many atoms that are uniformly distributed over the surfaces of the molecules, the total interaction energy between the two structures is obtained as a surface integral over the spherical and the toroidal surfaces. This analytical energy is employed to determine the most stable configuration of the torus encapsulating the fullerene. The results show that a torus with major radius around 20–22 Å and minor radius greater than 6.31 Å gives rise to the most stable arrangement. This study will pave the way for future developments in biomolecules design and drug delivery system.